Religieuze co-existentie en de publieke kerk. Walcheren en Staats-Vlaanderen, 1602-1630 - Bauwens, Michal (BMGN - Low Countries Historical Review, 2011)
Religious Co-Existence and the Public Church: Walcheren and Flanders of the States, 1602-1630During the past decades, the study of religious tolerance has shifted from its earlier focus on philosophical and legislative sources to a focus on daily practice, making use of detailed case studies. This article partly traces this historiographical shift by focusing on a locality in Zeeland. Although the Dutch Republic was renowned for its tolerance, Zeeland somehow was neglected in the historiography on religious tolerance. Whereas many studies have neglected the role of ecclesiastical organizations – or assumed that they played only a negative role in the space for religious co-existence – this article argues that these organizations in fact played a crucial role. For this reason, I have chosen to investigate the ‘classis Walcheren’ (the ecclesiastical assembly responsible for the region Walcheren and the Flanders of the States) during the first thirty years of the seventeenth century. This institution, which brought together all the reformed preachers of the region, had a strong influence on the churches, but also on society as a whole. Asking what exactly the ambitions and function of the classis and the reformed churches were, allows their impact on religious co-existence to be understood.